A revenda de combustível e os limites constitucionais para a sua regulação: uma análise aplicada aos aspectos concorrênciais e ao controle de preços - Gabbay, Samuel Max (2012)
The gas retail represents the end of a section of the oil and natural gas derivative chain, for it is at this stage where the commercialization of those merchandises takes place towards the costumers. This process involves an enormous amount of economic agents, which reflects on an activity of great influence on the citizen's everyday. By the time of the gas retail price liberalization, in 2002, there were great expectations towards that measure, for the insertion of that segment in a competitive market was likely to create a decrease in prices. As there was not a drastic drop off in cost, the question was no longer the price itself, but, predominantly, the conduct taken by the economic agents that operate the market. Not in vain, the segment introduces a greater number of different procedures combined with the organs that compose the Brazilian System of Competition Protection. What is understood, however, is that many of these complaints are made in a lightly way, without a proper analysis of the market and its practices, that being why, in this paper, evidences the causes of these complaints and explained what, in fact, occurs in this market. Also, the organs that protect the free initiative in the sector use different methods to assess anticompetitive practices, which are counterproductive on the combat of anticompetitive practice, that being why the present paper analyzes the used methods on a critic perspective, choosing one which is believed to be the most adequate. The present work also tries to present the gas retail prices on a constitutional, free competition, free initiative and consumers defense perspective, analyzing the competition s aspects on the gas market; the shaping of the gas prices; the market boundaries; the anti-competitive practices under the gas market; and analyze the possibility, according to the defined economic standards in the constitutional text of existing a greater control or gas price indexing and/or regulation which limits the distributors and resellers profit on gas. Still, in consequence of this analysis, a study on Natal s market behavior will be developed in its competitive feature. That being said, moreover being a theoretical-descriptive study, data and statistics gathered is used, which will lead, willing to grasp an experiential study on a few aspects of the Potiguar gas retail market